Mediehistoria i Lund - Lundell, Patrik (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
This text describes the ongoing establishment of media history at Lund University and reflects on its two-front strivings. The birth of media history as a proper, albeit small, discipline within the ordinary structure of the faculty, from graduate level to PhD studies, was very much a matter of chance, and easy enough to achieve. Whether this institutionalisation actually will be productive for the efforts to forward the field of media history, as constituted by input from a wide range of disciplines and for the time being centered on networking and a cross-disciplinary seminar series, is too early to tell.